Exploring Primary and Secondary School Students’ Perception towards Online Mathematics Tuition: A Case Study - Yit, Ooi Chin; Sam, Lim Chap (2011)
Online mathematics tuition could help to enhance primary and secondary school students learning. The question therefore rose as to whether online mathematics tuition would be accepted by the students as an alternative delivery method to support their learning. The objective of this article is to explore the online mathematics tuition for primary and secondary school students and find out their perceptions of the tuition that was designed based on Score A ProgrammeTM. The perceptions surveyed into six aspects – Relevance, Reflection, Interactivity, Tutor support, Peer support and Interpretation. The online mathematics tutorial format was a combination of face-to-face tuition and online learning sessions which organised various activities intended to encourage student learning online. The case study utilised online questionnaires and interview methods to assess the student perceptions of the online mathematics tutorial programme. The assessment result from the questionnaires and interview illustrated students behaved individualistic and expected a lot of tutor support rather than from peer support. In addition, the reflective thinking and interaction aspects can be improved by tutor initiating good discourse. Overall, the online mathematics tutorial programme was perceived relevant to school study, excellent tutor support and comprehensive interpretation course. The students reported positive perceptions to the online mathematics tuition. The study concluded that the online mathematics tuition is an effective learning programme for primary and secondary school students.